Statement by the Managing Director on the Work Program of the Executive Board. (Policy Papers; Policy Paper, 2012)
The Managing Director's Global Policy Agenda (GPA) presented to the IMFC during the Annual Meetings charted a set of actions needed across the membership to secure the recovery and to lay the foundation for a more robust global financial architecture. The GPA also detailed the Fund's role in assisting the membership with these formidable tasks, building on the recent reforms to buttress the Fund's surveillance framework. This work program translates the broad policy directions laid out in the GPA into a specific agenda for the Fund for the next six months and, in order to foster more strategic planning and prioritization, our current plans regarding key policy items over the next year.